Peramalan Laju Inflasi dan Nilai Tukar Rupiah Terhadap Dolar Amerika Menggunakan Model Vector Autoregressive (VAR) - Fitrian Fariz Ichsandi; Rita Rahmawati; Yuciana Wilandari (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
Vector Autoregressive Method (VAR) is a simultaneous equation model has several endogeneous variables. In the VAR Model each variable endogeneous is explained by lag from own value and lag from the other variable. Equation of VAR generally use to forecast. In this final task VAR model was applied to find the forecasting value of inflation rate in Indonesia and the US dollar exchange rates. Testing in VAR models includes stationarity test, granger causality test and white noise test. Based on the analysis showed that inflation variable and US dollar exchange rates variable are both experiencing differencing first lag so as mentions for both variables become d_inflasi and d_kurs. The best lag for VAR model is lag 3 for each model. Forecasting for 5 periods refers to indicate that inflation rate fluctuated is stable at the average rate 0,33% while the US dollar exchange rates tended to decrease on 4 periode and increase on periode to 5 with an average exchange rate is Rp. 10.018,76.Keywords: inflation, US dollar exchange rates, VAR